2015
DOI: 10.5304/jafscd.2015.052.005
|View full text |Cite
|
Sign up to set email alerts
|

http://www.agdevjournal.com/volume-5-issue-2/510-products-urban-collective-gardens.html

Abstract: Among the various forms of urban agriculture that have emerged and been developed over the past 15 years in countries of the global North, collective gardens (CGs) are one of the most significant. In Montreal and Paris, their numbers have increased rapidly in the past 20 years. Previous research has shown that food production is an important motivation for urban dwellers to engage in gardening activities, but the food function of CGs, that we define as the quantitative and qualitative food supply they are like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Therefore, the fungi lasted as long as the tomato plants, thus weakening them. Nevertheless, yields for L and L-I units were equivalent to those observed in private vegetable gardens in the Paris area (Pourias et al 2015) and other productive rooftops (Samangooei et al 2016), but lower than those observed in a comparable rooftop system where compost was used together with mineral fertilizers under a different climate (Orsini et al 2014) (Table 2). The present Technosols had a priori favorable characteristics for vegetable growth with a slightly acidic to slightly basic pH (Fig.…”
Section: Food Productionmentioning
confidence: 65%
“…Therefore, the fungi lasted as long as the tomato plants, thus weakening them. Nevertheless, yields for L and L-I units were equivalent to those observed in private vegetable gardens in the Paris area (Pourias et al 2015) and other productive rooftops (Samangooei et al 2016), but lower than those observed in a comparable rooftop system where compost was used together with mineral fertilizers under a different climate (Orsini et al 2014) (Table 2). The present Technosols had a priori favorable characteristics for vegetable growth with a slightly acidic to slightly basic pH (Fig.…”
Section: Food Productionmentioning
confidence: 65%
“…Previous research has also noted the wide variability of yields among individual gardens [10,11,13,20,31,32]. Table 1 compares the EG yield results with the yield results of those previous studies which explicitly reported area under production and their duration of data collection.…”
Section: New Findings On the State Of Existing Urban Food Gardensmentioning
confidence: 92%
“…The average yield rate across eight studies that have quantified harvests in home and community gardens is 0.6 lbs/ft 2 (2.93 kg/m 2 ) of growing space (author calculations from Algert, Baameur, & Renvall, 2014;CoDyre, Fraser, & Landman, 2015;Conk & Porter, 2016;Gittleman, Jordan, & Brelsford, 2012;Pourias, Duchemin, & Aubry, 2015;Smith & Harrington, 2014;Vitiello & Nairn, 2009;Vitiello, Nairn, Grisso, & Swistak, 2010). This approaches the yield rate of 0.67 lbs/ft 2 (3.27 kg/m 2 ) estimated to be typical of vegetable farms (Seufert, Ramankutty, & Foley, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%